1981
DOI: 10.1136/hrt.46.5.539
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic antibiotics for cardiac pacemaker implantation. A prospective trail.

Abstract: SUMMARY A prospective trial was conducted to assess the value of prophylactic antibiotic treatment in preventing postoperative infection of permanent transvenous pacemaker systems. Four hundred and thirty-one patients were randomly allocated to treatment (234) or no-treatment (197) groups. Treated patients received systemic benzylpenicillin and flucloxacillin just before operation and one and six hours afterwards.Nine primary generator pocket infections occurred without evidence of wound dehiscence or skin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The use of antibiotics in a pacemaker procedure follows the principle of prophylaxis, in which the risk for infection is low but the monetary penalty or morbidity is high. [35][36][37] The selection of antibiotics is based on site-specific flora for wound infection and the spectrum, kinetics, and toxicity of the antimicrobial agent. The risk factors for infection have been well defined.…”
Section: Antibiotic Prophylaxis and Wound Irrigationmentioning
confidence: 99%
“…The use of antibiotics in a pacemaker procedure follows the principle of prophylaxis, in which the risk for infection is low but the monetary penalty or morbidity is high. [35][36][37] The selection of antibiotics is based on site-specific flora for wound infection and the spectrum, kinetics, and toxicity of the antimicrobial agent. The risk factors for infection have been well defined.…”
Section: Antibiotic Prophylaxis and Wound Irrigationmentioning
confidence: 99%
“…However, on the basis of two cases of severe S. aureus bacteremia, Hartstein et al concluded that antibiotics might reduce the severity of infection (57,58). More recently, four of five placebo-controlled trials and one meta-analysis indicated that prophylactic antibiotic therapy reduces the incidence of infections related to pacemaker implantation (59)(60)(61)(62)(63)(64). On the basis of controlled trials and various observational studies, it seems that prophylactic antibiotics are widely used prior to permanent pacemaker implantation and also that definitive guidelines are needed since there is little or no standardization.…”
Section: Indications and Efficacymentioning
confidence: 99%
“…One of the first randomized trials of intravenous antibiotics, reported in 1981, randomized patients who were scheduled to have a transvenous pacemaker implanted, to both intravenous flucloxacillin and intramuscular benzylpenicillin or to no antibiotics. [6] Two hundred and thirty four patients received antibiotics and one hundred and ninety-seven did not. Infection rates were 0.8% for the antibiotic treated group and 3.6% in the group who did not receive antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to 1994, the data supporting the use of intravenous antibiotics was variable. [6], [16] In 1994, Drs. Mounsey and colleagues reported one of the first prospective randomized trials that demonstrated a benefit of pre-incision antibiotics.…”
Section: Introductionmentioning
confidence: 99%